2015
DOI: 10.1111/jopr.12415
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Recall Regimen and Maintenance Regimen of Patients with Dental Restorations. Part 2: Implant‐Borne Restorations

Abstract: Purpose To evaluate the current scientific evidence on patient recall and maintenance of implant‐supported restorations, to standardize patient care regimens and improve maintenance of oral health. An additional purpose was to examine areas of deficiency in the current scientific literature and provide recommendations for future studies. Materials and Methods An electronic search for articles in the English language literature from the past 10 years was performed independently by multiple investigators using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 34 publications
0
52
1
1
Order By: Relevance
“…Given the resources required to treat patients with complex dental needs, an appropriate patient recall regimen, professional maintenance regimen, and at-home maintenance regimen are paramount for long-term success. 13,14 Furthermore, it is likely that the professional and at-home maintenance protocols in healthy adult patients with tooth-and implant-borne restorations may be significantly different when compared to patients with no restorations, or patients with acute or chronic oral and systemic diseases. For toothborne restorations, guidelines on the options and relative merits of professional and at-home maintenance protocols to predictably achieve stable results are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the resources required to treat patients with complex dental needs, an appropriate patient recall regimen, professional maintenance regimen, and at-home maintenance regimen are paramount for long-term success. 13,14 Furthermore, it is likely that the professional and at-home maintenance protocols in healthy adult patients with tooth-and implant-borne restorations may be significantly different when compared to patients with no restorations, or patients with acute or chronic oral and systemic diseases. For toothborne restorations, guidelines on the options and relative merits of professional and at-home maintenance protocols to predictably achieve stable results are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methodology for the search processes are described in the respective systematic review articles. 13,14 For tooth-borne restorations, 16 studies were identified in the systematic review that reported data on a combined 3569 patients. Of these, nine were randomized controlled clinical trials (RCT), and seven were observational studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, knowing the incidence, type, and rate of complications with each treatment modality is necessary, especially when the treatment cost is increased . Ultimately, the selection of a treatment option from the financial and effectiveness viewpoints relies on the longitudinal efficacy of the option coupled with the associated cost and maintenance when complications occur …”
mentioning
confidence: 99%
“…The response to the publication of our recent systematic reviews and clinical practice guidelines (CPGs) has been encouraging. Soon after the release of the Journal of Prosthodontics supplement, Yahoo Finance, Econotimes.com, and other national media outlets picked it up.…”
mentioning
confidence: 99%